The Initial Lexicogrammatical Competence of the English Education Freshmen - Barans I. Palangan (English Education Department - Universitas Nasional Karangturi, 2021)
According to Harmer, grammar and vocabulary are the elements of language. Therefore, they are essential in both language learning and language teaching. Halliday, furthermore, views that grammar and vocabulary (lexis) are mutually dependent and defines this interdependency as lexicogrammar. This research aims to describe the initial lexicogrammatical competence of the freshmen in the English Education Department in Universitas Nasional Karangturi. This research needs to be done since the initial linguistic competence is crucial for improving all language skills. To find out the learners’ initial lexico-grammatical profile, the TOEFL test battery, particularly section 2 (the structure and written expression test), was chosen as the instrument to describe the initial lexicogrammatical competence of the 16 students. After the test was administered, the average score was calculated, and the frequently missed questions were classified based on the classification of skills in the TOEFL book. The result shows that the students’ average score is 17.44 out of 40 and there are 23 questions frequently missed. These 23 frequently missed questions, moreover, comprise 22 lexicogrammar-related skills. The description of these 22 lexicogrammatical problems, thus, can inform the English Department regarding the grammar topics that need to be addressed when teaching the students. In this way, it is hoped that the findings can make a substantial contribution to what will be improved in teaching lexicogrammar